Design of applications on ultra-wideband real-time locating system - Lee, Wen Jian. (2009)
There are various types of Real-Time Locating System (RTLS) in the market. They are differing based on technology and location method used. Each type of RTLS fits different needs, depending on its ranging and accuracy. Nowadays, a break-through in the application of a radio frequency (RF) technology called Ultra-Wideband (UWB) has enabled RTLS to deliver up to 15cm 3D positional accuracy in traditionally challenging environments at reliability levels which is unachievable by the legacy technologies such as conventional RFID or Wi-Fi. UWB technology is relatively new for the RTLS. The UWB RTLS on the market is quite basic, with the ability to detect the positions of tags and record the location data to the database. However, UWB RTLS is seen as a viable, growing technology, because it provides highly accurate location data and works effectively indoors or out. Realising the growing opportunity of UWB RTLS, several applications are designed and developed in this project to enhance the performance of UWB RTLS. These applications are designed based on varied uses of location information. These include storing location information for path history, real-time location information for path tracking, triggering events using location information, and location information as efficiency indicator. In these application designs, programming techniques and skills are essential, especially the techniques and skills in designing and creating Windows application form and graphical user interface (GUI). For integrating designed applications with the UWB RTLS software and hardware, existing code integration skills are also necessary. Techniques and knowledge in algorithms and data structure shall be equipped to deal with data management. Lastly, suitable programming platform shall be chosen.